Clinical Demonstration of the Potential of Parental Feedback in Reducing Deterioration During Group Psychotherapy With Children. Issue 9 (September 2020) - Tzur Bitan, Dana; Zilcha-Mano, Sigal; Asper, Ariel; Bloch, Yuval
Abstract : Abstract: In recent years, great efforts have been exerted to minimize the rates of deterioration in clinical practice, especially in child psychotherapy. The present study explored the potential effect of routine outcome monitoring (ROM) with parents as a preventive intervention to reduce deterioration in children. Twenty-five children receiving treatment for emotional problems were randomized to parent-based, ROM-assisted group psychotherapy or to treatment as usual (TAU). A mixed-methods approach was utilized, with the number of deteriorating cases compared at the group level and two case illustrations assessed at the individual level. At the group level, there were fewer cases of deterioration in child's anxiety, parental stress, and quality of parent's alliance in the ROM-assisted group, compared with TAU. Case studies illustrated how ROM can be used as a tool to communicate with parents to prevent deterioration. Routine outcome monitoring in child psychotherapy may thus benefit therapy process and outcome. Limitations and directions for future research are discussed.